Serological survey against influenza virus in Population Studies Islamabad Capital 1959 - 1960 - Flores, W. (1966)
The authors present a work on the problem of influenza, studied from serologically. Was conducted in the year 1959-60 against a serological survey of influenza virus, in 1276 persons of both sexes, whose ages ranged from one to 99 years. For the proper medical problems arising from influenza, consider the serious socio-economic conditions that are caused by epidemics of these viruses; This makes the study of this virus is of global concern and therefore the importance and objectives that will lead to making this work is pointed out.